Fuzzy-based Medical X-Ray Image Classification - Ghofrani, Fatemeh (Medknow Publications & Media Pvt Ltd, 2012)
In this paper, a novel fuzzy scheme for medical X-ray image classification is presented. In this method, each image is partitioned into 25 overlapping subimages and then, we extracted the shape-texture features from shape and directional information of each subimage. In the classification step, we apply a fuzzy membership to each subimage considering the Euclidean distance between feature vector of each subimage and average of feature vectors of training subimages. At last, a hard classification of the test image can be obtained by performing a max operation on the summation of fuzzy memberships. The proposed method is evaluated for image classification on 2655 radiographic images from IRMA dataset with 300 training samples and 2355 test samples. Classification accuracy rates obtained by fuzzy classifier are higher than that of obtained by multilayer perceptron or even SVM classifier.